The Exploration of The Cultural Shock Experience of Indonesian Students in Egypt - Awad, Siraj Ribhi; Nuraryo, Imam; Idrus, Mustafa Habibie (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The decision to study abroad is driven by the desire to get a better education, expand their network, and experience different lives and cultures. All of these are expected to contribute positively to their personal and professional development in the future. Most Indonesian students study in Egypt because they are studying Religious Studies, especially Islam. However, there are actually many Indonesian students who study in Egypt not only studying religious studies. There are several key theories that are often used to understand the cross-cultural adaptation process for students abroad, including; U-Curve Theory, Stress and Adaptation Theory, and Intercultural Communication Theory. The research method used in writing this paper is secondary data analysis. Numerical data such as census data, crime statistics, sales data, or quantitative survey results. Data in the form of interviews, transcripts, documentation, or notes that have been collected previously and can be reused in new analyses. The journey of Indonesian students to study in Egypt certainly faces various challenges. The challenge was faced by him during the registration process to the selection which is known to be quite strict. The cultural differences faced by Indonesian students in Egypt are the use of everyday language for communication. Egypt as a country that uses Arabic as its national language for communication certainly requires Indonesian students to be able to communicate using Arabic. This is a cultural difference in the use of everyday language.